Pengaruh Literasi Keuangan, Digital Payment dan Gaya Hidup Konsumtif terhadap Keputusan Pembelian pada Platform E-commerce (Studi pada Mahasiswa di Yogyakarta) - Aninda Fabila Shofa; Fahrul Imam Santoso (Program Studi Akuntansi Fakultas Ekonomi Universitas Samudra, 2026)
This research aimed to analyze the effect of financial literacy, digital payment, and consumptive lifestyle on purchasing decisions within e-commerce platforms. The data collected through a questionnaire distributed to 146 respondents of undergraduate students in Yogyakarta, the collected sampling method used is Purposive Sampling. The data analysis used is research are descriptive statistical tests, validity and reliability tests, classical assumption tests, multiple linear regression analysis, and hypothesis test using the help of SPSS 27 for windows. This research partial test demonstrates that financial literacy has a positive and significant effect on purchasing decisions on e-commerce platforms (H1) is accepted. Digital payment also exerts a positive and significant effect on purchasing decisions on e-commerce platforms (H2) is accepted. In contrast, consumptive lifestyle shows no significant effect on purchasing decisions on e-commerce platforms (H3) is rejected. The simultaneous test results reveal that financial literacy, digital payment, and consumptive lifestyle collectively have a positive and significant effect on purchasing decisions on e-commerce platforms (H4) is accepted. Future researchers are expected to more completely or modify factors associated with these variables—such as online store reputation, return rates, and delivery times etc. Furthermore, future research are expected to develop the “consumptive lifestyle” variable in line with the latest theoretical advancements, so allowing for a more robust explanation grounded in specific theoretical frameworks.